RESISTENSI KOMUNITAS TERHADAP KEBIJAKAN PEMBIAYAAN ISTISHNA - Abidin, Abidin; Sapruddin, Sapruddin; Ruslan, Murniati (State Islamic University of Datokarama Palu, 2022)
This study aims to map and analyze the forms, factors, and implications that cause stakeholder resistance to istishna' financing policies at Indonesian Syariah Bank in Palu and Jakarta. Data collection techniques were carried out using interview and library techniques. Data analysis uses content analysis with an objective approach to place the results of interviews and literature against each other. The data sources used are a collection of interviews and literature reviews. The results showed that there had been stakeholder resistance to istishna' financing in the two Indonesian Syariah Bankdue to being treated unfair in the form of an increase in the price of goods orders according to the length of instalments, the reworking of goods orders that were not by stakeholder tastes, and delays in delivering goods orders to stakeholders after falling. Tempo in the form of an additional budget to stakeholders. In addition, it is also found that the istishna financing process is complex, the risk of which is dominated by the burden on stakeholders. In addition, the narrowing of the istishna' financing target in the form of micro even though public interest and maqhasid sharia require a macro. Internal and external resistance factors cause stakeholder resistance to the istishna financing policy. These two factors have implications for the circulation of funds in Indonesian Syariah Bankin Palu and Jakarta, which take a long time, are unreliable, have the opportunity to go bankrupt, and take into account the possible risks that cause stakeholders' interest in using istishna financing to decrease. Actions must be taken against stakeholder resistance who experience istishna financing policies in the two Indonesian Syariah Bank, the prohibition of instalments if it causes an increase in the price of the order, the product must be completed at maturity, the product must be following the taste/agreement, there should be no additional funds due to the demand not following the agreement/customer's taste.